Knowledge, Motivation, and Islamic Financial Behavior as Predictors of Islamic Investment Intention: Evidence from Muslim University Students - Ayu Fitriana; Reni Ria Armayani Hasibuan; Nur Ahmadi Bi Rahmani (Jurnal Investasi Islam, 2026)
This study examines the influence of investment knowledge, motivation, and Islamic Financial Behavior on Islamic investment intention among Muslim university students in Medan City. Previous studies have shown inconsistent findings regarding the role of Islamic Financial Behavior in shaping investment intention. This study employed a quantitative approach using purposive sampling techniques involving 100 students. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS version 26. The findings indicate that investment knowledge and motivation positively and significantly influence Islamic investment intention, while Islamic Financial Behavior does not have a significant effect. Simultaneously, all independent variables significantly affect Islamic investment intention, with an adjusted R² value of 0.753. These findings strengthen the Theory of Planned Behavior (TPB) in explaining Islamic investment intention through cognitive and motivational dimensions. Practically, the study emphasizes the importance of improving Islamic financial literacy and investment education programs to encourage student participation in Sharia-compliant investments.